Suction-induced retinopathy: optical coherence tomography correlations. (29th June 2018) - Fernandes, Tiago; Freitas, Cristina; Mendonça, Luís; Sousa, Keissy
Abstract : We report a clinical case of a teenager whose eyes were exposed to highly negative suction pressures for brief seconds. The patient presented with a bilateral cystoid macular oedema associated with a thickening of outer nuclear layer evidenced by optical coherence tomography. The patient's constellation of findings is most easily explained by the abrupt expansion and traction of a cohesive vitreous base onto the retinal layers.